Lockdown on London Lane - Reekles, Beth ([Place of publication not identified] : W by Wattpad Books, 2022)
"For the inhabitants of London Lane, a simple slip of paper underneath each of their doors is about to change their lives in a hundred different ways. URGENT!!! Due to the current situation, building management has decided to impose a seven-day quarantine on all apartment buildings on London Lane. Ethan and Charlotte wonder whether absence really does make the heart grow fonder when they end up on either side of a locked door. A fierce debate over pineapple on pizza ignites a series of revelations about Zach and Serena's four-year relationship. Liv realizes rolling with the punches is sometimes much harder than it looks after her bridesmaids' party goes off the rails, leaving the group at each other's throats. Isla and Danny's new romance is put to the test as they jump ten steps ahead on the relationship timeline. And Imogen and Nate's one-night stand is about to get six do-overs they never really asked for--not awkward at all. Through make ups, breakups, love-ins, and blowouts, friendships are tested as everyone scrambles to make it through the week unscathed. Amidst all the drama, one thing remains constant: life is full of surprises."
Keywords: Romance; woman's fiction; Mystery; Contemporary; Romance fiction